Intent matters: Resolving the intentional versus incidental learning paradox in episodic long-term memory - Popov, Vencislav; Dames, Hannah (Journal of experimental psychology. General, 2023)
Decades of research have established that the intent to remember information has no effect on episodic long-term memory. This claim, which is routinely taught in introductory cognitive psychology courses, is based entirely on pure-list between-subjects designs in which memory performance is equal for intentional and incidental learning groups. In the current 11 experiments, participants made semantic judgements about each word in a list but they had to remember only words presented in a specific color. We demonstrate that in such mixed-list designs there is a substantial difference between intentionally and incidentally learned items. The first four experiments show that this finding is independent of the remember cue onset relative to the semantic judgment. The remaining seven experiments test alternative explanations as to why intent only matters in mixed-list designs but not in pure-list designs-inhibition of incidentally learned items, output interference, selective relational encoding, or selective threshold-shifting. We found substantial support for the threshold-shifting account according to which the intent to remember boosts item-context associations in both mixed- and pure-list designs; however, in pure-list between-subjects designs, participants in the incidental learning group can use a lower retrieval threshold to compensate for the weaker memory traces. This led to more extralist intrusions in incidental learning groups; incidental learning groups also showed a source memory deficit. We conclude that intent always matters for long-term learning, but that the effect is masked in traditional between-subjects designs. Our results suggest that researchers need to rethink the role of intent in long-term memory. (PsycInfo Database Record (c) 2023 APA, all rights reserved).